Native and Non-native Speech Perception by Hearing-Impaired Listeners in Noise- and Speech Maskers - Kilman, Lisa (Trends Hear, 2015)
This study evaluated how hearing-impaired listeners perceive native (Swedish) and nonnative (English) speech in the presence of noise- and speech maskers. Speech reception thresholds were measured for four different masker types for each target language. The maskers consisted of stationary and fluctuating noise and two-talker babble in Swedish and English. Twenty-three hearing-impaired native Swedish listeners participated, aged between 28 and 65 years. The participants also performed cognitive tests of working memory capacity in Swedish and English, nonverbal reasoning, and an English proficiency test. Results indicated that the speech maskers were more interfering than the noise maskers in both target languages. The larger need for phonetic and semantic cues in a nonnative language makes a stationary masker relatively more challenging than a fluctuating-noise masker. Better hearing acuity (pure tone average) was associated with better perception of the target speech in Swedish, and better English proficiency was associated with better speech perception in English. Larger working memory and better pure tone averages were related to the better perception of speech masked with fluctuating noise in the nonnative language. This suggests that both are relevant in highly taxing conditions. A large variance in performance between the listeners was observed, especially for speech perception in the nonnative language.